2023
DOI: 10.1177/03913988231191952
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal albumin dialysis in critically ill patients with liver failure: Comparison of four different devices—A retrospective analysis

Oliver Sommerfeld,
Caroline Neumann,
Jan Becker
et al.

Abstract: Background: Besides standard medical therapy and critical care monitoring, extracorporeal liver support may provide a therapeutic option in patients with liver failure. However, little is known about detoxification capabilities, efficacy, and efficiency among different devices. Methods: Retrospective single-center analysis of patients treated with extracorporeal albumin dialysis. Generalized Estimating Equations with robust variance estimator were used to account for repeated measurements of several cycles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Albumin has been shown to have therapeutic effects in patients with liver failure. For example, Sommerfeld et al [ 26 ] reported that extracorporeal albumin dialysis enhanced bile acid clearance or albumin binding in the livers of patients with severe liver failure, thus protecting against further damage.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin has been shown to have therapeutic effects in patients with liver failure. For example, Sommerfeld et al [ 26 ] reported that extracorporeal albumin dialysis enhanced bile acid clearance or albumin binding in the livers of patients with severe liver failure, thus protecting against further damage.…”
Section: Discussionmentioning
confidence: 99%
“…Open albumin dialysis (OPAL) was first introduced in 2014. It is analogous to the molecular absorbent recirculating system (MARS) liver support system but with a greater filter surface, and a recent study comparing extracorporeal albumin dialysis showed that OPAL may provide higher reduction capabilities of liver solutes (i.e., bilirubin and ammonia) in comparison to MARS [ 10 ].…”
Section: Case Presentationmentioning
confidence: 99%